Peran Moralitas Aparatur Dan Sistem Pelaporan Pelanggaran Dalam Mencegah Kecurangan Dana Desa - Dzikri Ardan Fadhila; Tarmizi Achmad (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to empirically prove the effect of apparatus morality and whistleblowing system on the prevention of village fund fraud. Methodology/Approach: This study is a quantitative research with primary data sources obtained from distributing questionnaires to respondents. The sampling technique used was purposive sampling technique. The sample of this study consisted of 174 village apparatuses in Pangkah District, Tegal Regency. The analysis technique used to test the hypothesis was multiple linear regression. Findings: The results showed that apparatus morality and whistleblowing system had a positive effect on the prevention of village fund fraud. Practical and Theoretical Contribution/Originality: The results of this study are expected to contribute to improving the effectiveness of village fund management against the potential for fraud and also useful as a source of reference for other similar studies. Research Limitation: The limitation of this study lies in the use of questionnaires as the only method of data collection, which may result in inaccurate answers from respondents. Further research is suggested to add interview methods to deepen the topic under study, as well as reduce potential bias.